Optimal Stock Portfolio Establishment with Active and Passive Strategy Using Price to Book Value and Price Earning to Growth Ratio Approach in IDX30 Index 2013-2018 Period - Alimuddin, Almand Fuad; hendrawan, Riko (Green Publisher Indonesia, 2023)
The volatility phenomenon of stock returns shows the return and risk faced by investors in investment activities. One method that can be used by investors to get maximum profit while compressing the risk into the minimum level is by diversifying its investments through portfolios. This study aims to determine the simulation results of optimal stock portfolio establishment with active and passive strategy using Price to Book Value and Price Earning to Growth ratio approach and the results of the Sharpe, Treynor, and Jensen performance evaluations on the established portfolio. This research appertains in quantitative research. The object of the research was the IDX30 Index and 17 of 30 companies which consistently classified into the IDX30 Index for the 2013-2018 period were selected as the research sample. The results showed that High PEG consistently provides better than the average returns and risks, whether in passive strategy, annual’s active strategy, or semester’s active strategy. Whereas, High PBV in the passive and annual's active strategy showed a high rate of return above the average, while in the semester active strategy, showed the lowest level of risk. Overall the semester's active strategy has the highest accumulated rate of return with a relatively low rate of risk. This result match with the purpose of optimal portfolio establishment. Moreover, the results of the performance evaluation showed that in the semester's active strategy, High PEG gives the best score based on the results of the performance evaluation of Sharpe, Treynor and Jensen index.